2016
DOI: 10.1002/mame.201600249
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Extrusion Strategies to Fabricate Magnetite–Polyethylene Nanocomposites with Enhanced Mechanical and Magnetic Hyperthermia Properties

Abstract: Biofouling is a major problem in water filtration units, which leads to premature system failure. Conventional treatment methods involving the use of chemicals or high‐pressure hydraulics exert mechanical strain on filter materials, leading to shortened service lifetimes. In this study, a novel magnetic polymer nanocomposite is fabricated using a blend of high density/ultrahigh molecular weight polyethylene with magnetite nanoparticle (MNP) fillers. The resulting magnetite–polyethylene nanocomposite (MPE‐NC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…It can be observed that a lower increase in temperature was achieved in the hydrogel sample (5 °C) compared to when the MNPs are in solution (25 °C). The decrease in heating efficiency of the c-MNPs in the gel matrix can be attributed to the viscous nature of the hydrogel whereby Brownian rotation is restricted leading to lower heating performance , (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that a lower increase in temperature was achieved in the hydrogel sample (5 °C) compared to when the MNPs are in solution (25 °C). The decrease in heating efficiency of the c-MNPs in the gel matrix can be attributed to the viscous nature of the hydrogel whereby Brownian rotation is restricted leading to lower heating performance , (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…21,22,24−29 Moreover, magnetic hyperthermia has also been demonstrated to be much more effective than direct heating toward the destruction of the bacterial cell membrane integrity, as well as promoting modifications on the bacterial cell surface and biofilm structure that can eventually lead to successful eradication. 23,24 The thermal disruption of bacterial biofilms using magnetic hyperthermia is attractive because it does not rely on the use of antibiotics and could treat antibiotic-resistant bacterial strains. In addition, magnetic hyperthermia can be exploited to enable localized heating for targeted biofilm eradication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3(c)) to allow subsequent easier killing of bacteria by antibiotics in their planktonic state [71]. Besides application of magnetic hypothermal treatment in infection-control, it is being considered to prevent bacteriallyinduced food spoilage caused by Pseudomonas fluorescens [72] and contamination of water by Escherichia coli [73].…”
Section: Hyperthermia Induced By Magnetic Nanoparticles As An Antimicrobial Strategymentioning
confidence: 99%
“…In a separate study, Kim et al (2013) explored the use of SPIONs for targeted hyperthermia to eradicate S. aureus infection in both in vitro cell culture models as well as in vivo mice models without causing tissue injuries. In 2016, Situ et al improved the material properties of SPIONs and demonstrated that Zn-doping can enhance performance and antibiofilm efficacy in E. coli biofilms (Situ et al, 2016). Similarly, magnetic hyperthermia coupled with antibiotics has been shown to eradicate biofilms formed by S. epidermidis (Geilich, Gelfat, Sridhar, van de Ven, & Webster, 2017) and P. aeruginosa (Nguyen, Duong, Selvanayagam, Boyer, & Barraud, 2015).…”
Section: Beyond the Traditional Antibiotic Drug Treatment And Reimpmentioning
confidence: 99%